Peran Guru Pendidikan Agama Islam pada Sekolah Ramah Anak di SMP Negeri 22 Padang - Mahagandi, Vici Okta; Wiza, Rahmi (Darul Yasin Al Sys, 2023)
This research aims to describe the role of Islamic religious education teachers in realizing child-friendly schools (CFS) at SMP Negeri 22 Padang. The research method used in the research is qualitative with descriptive research type. Data collection techniques use observation, interviews and documentation. The research subjects were students, Islamic religious education teachers, and the principal of SMP Negeri 22 Padang. Based on the research results, it can be concluded that in creating a child-friendly school at SMP Negeri 22 Padang, Islamic religious education teachers have several roles as follows: the role of teacher as motivator, teacher as facilitator, teacher as advisor, teacher as guide.